On a collection of hydroids (Cnidaria, Hydrozoa) from the Madeira archipelago - Wirtz, Peter (2020)
Hydroids were collected from Madeira and Porto Santo Islands (eastern temperate Atlantic Ocean) by SCUBA diving over a depth range from 0 to 62 m, as well as by two trawls off the city of Funchal, at depths of 60 and 100 m. A preliminary list of 53 identified species from 33 genera and 17 families is given and comments are made on some of them. Eight of them could not be determined to species level because they either lacked gonophores or the medusa stage is necessary for identification. An undescribed species (genus Sertularella) will be described in a separate publication. Additional species have been sent to hydroid specialists, and their identifications are pending.